Investigating the benefits of targeted selective treatment according to average daily weight gain against gastrointestinal nematodes in Morada Nova lambs - Santos, Isabella Barbosa dos [UNESP]; Anholeto, Luís Adriano; Sousa, Gustavo Avelar de [UNESP]; Nucci, Alessandra da Silva; Gainza, Yousmel Alemán [UNESP]; Figueiredo, Amanda [UNESP]; Santos, Leonardo Aparecido Lima dos [UNESP]; Minho, Alessandro Pelegrine; Barioni-Junior, Waldomiro; Esteves, Sérgio Novita; Niciura, Simone Cristina Méo; Chagas, Ana Carolina de Souza (Springer Nature, 2022)
The objective of this study was to evaluate a method of targeted selective treatment (TST) of Morada Nova lambs, based on the average daily weight gain (DWG). For this, 114 lambs in the rainy and 102 in the dry season were randomized into three treatments: control (CT), routine (RT, treated every 42 days), and targeted selective (TST, treated according to DWG). Packed cell volume (PCV) and eggs per gram of feces (EPG) tests were performed. The anthelmintic resistance of parasites was assessed by the EPG count reduction test (FECRT), RESISTA-Test©, and molecular test. For CT, RT, and TST groups, the following results were obtained: mean EPG values were 4665.1, 3063.5, and 3462.1 in the rainy season and 4475.1, 1341.7, and 2863.4 in the dry season, respectively; mean PCV values were 32.1, 33.4, and 32.3% in the rainy season and 33.9, 36.0, and 35.1% in the dry season; mean DWG readings were 0.087, 0.101, and 0.094 kg in the rainy season and 0.102, 0.113, and 0.112 kg in the dry season; efficacies of levamisole in FECRT were 66.4, 24.1, and 76.4% in the rainy and 90.7, 12.4, and 64.8% in the dry season, respectively; in the RESISTA-Test©, the LC50 values were 0.482, 1.926, and 0.117 µg.mL−1 in the rainy and 0.437, 0.851, and 0.045 µg.mL−1 in the dry season, respectively; the frequencies of the homozygous-resistant genotype were 57.1, 71.4, and 40.0% in the rainy and 47.8, 55.9, and 41.9% in the dry season. In conclusion, TST reduced the development of resistance through refugia maintenance, without productive losses, contributing to the sustainability of sheep breeding.
Keywords: Acr-8 gene; Haemonchus contortus; Happy Factor™; RESISTA-Test©